The EMDR DeTUR protocol for the treatment of self-injury in a patient with severe personality disorder: a case report. Issue 1 (28th February 2019) - Annesley, Phyllis; Alabi, Adedayo; Longdon, Laura
Abstract : Purpose: The purpose of this paper is to describe the Eye movement desensitisation and reprocessing (EMDR) treatment of an adult female patient detained within a high secure hospital with complex mental health difficulties, including complex trauma, factitious disorder, self-injury and a history of offending. The EMDR treatment addressed the patient's urges to engage in severe and sometimes life-threatening self-injury, a primary motive of which was to access physical healthcare interventions within a general hospital. The paper describes the wide-ranging benefits of the treatment and incorporates feedback from the patient and clinicians within her multi-disciplinary team (MDT). Design/methodology/approach: Four triggers for self-injury were processed during the therapy using the DeTUR Protocol (Popky, 2005, 2009 ) and the Constant Installation of Present Orientation and Safety (CIPOS, Knipe, 2009a ) method. In total, 18 one hour therapy sessions were delivered plus three follow-up sessions to continue to offer support and complete the post-treatment evaluation. Findings: The level of urge for each trigger was reduced to 0 which the patient defined as "no urge to self-injure". Benefits went well beyond self-injury with reported positive impacts on mood, thinking, sleep, concentration, memory and experience of flashbacks. Practical implications: This case report demonstrates that the EMDR DeTUR Protocol together with the CIPOS method can be extremely valuable in the treatment of patients who self-injure. Originality/value: The case report offers an important contribution to an area that requires much further research.